Ophthalmic vascular manifestations in eosinophil-associated diseases: a comprehensive analysis of 57 patients from the CEREO and EESG networks and a literature review - Chapuis, Elisa; Bousquet, Elodie; Viallard, Jean-François; Terrier, Benjamin; Amoura, Zahir; Batani, Veronica; Brézin, Antoine; Cacoub, Patrice; Caminati, Marco; Chazal, Thibaud; Comarmond, Cloé; Durieu, Isabelle; et al. (Frontiers in Immunology, 2024)
Eosinophils have widespread procoagulant effects. In daily practice, eosinophil-related cardiovascular toxicity consists of endomyocardial damage, eosinophilic vasculitis and arterial or venous thrombosis. Here we aim to report on the clinical features and treatment outcomes of patients with unexplained ophthalmic vascular manifestations and eosinophilia. We conducted a retrospective, multicenter, observational study and a literature review of patients with eosinophilia (≥0.5 x10 9 /L) and concomitant ophthalmic vascular manifestations independent of the underlying eosinophilic disease but with no alternative cause for ophthalmic manifestations. Fifty-seven patients were included (20 from the observational study and 37 from the literature review) . Ophthalmic vascular features were the initial manifestation of eosinophil-related disease in 34 (59%) patients and consisted of 29 central retinal artery occlusions, six branch retinal artery occlusions, five central retinal vein occlusions, two branch retinal vein occlusions, seven retinal vasculitides, two retinal vasospasms, 12 Purtscher's retinopathies, 13 anterior ischemic optic neuropathies and two posterior ischemic optic neuropathies. The median [IQR] absolute eosinophil count at onset of ophthalmic vascular manifestations was 3.5 [1.7-7.8] x10 9 /L. Underlying eosinophil-related diseases included eosinophilic granulomatosis with polyangiitis (n=32), clonal hypereosinophilic syndrome (HES) (n=1), idiopathic HES (n=13), lymphocytic HES (n=2), adverse drug reactions (n=3), parasitosis (n=2), polyarteritis nodosa (n=1), IgG4-related disease (n=1), eosinophilic fasciitis (n=1) and primary sclerosing cholangitis (n=1). Other extraophthalmologic arterial or venous thromboses related to eosinophilia were reported in four (7%) and nine (16%) patients, respectively. Visual prognosis was poor: only eight (10%) patients achieved full recovery of ophthalmologic symptoms. After a median follow-up of 10.5 [1-18] months, one patient (3%) had a recurrence of an ophthalmic vascular manifestation, and three patients (10%) had a recurrence of other vascular symptoms (deep vein thrombosis in two and pulmonary embolism in one patient). At the time of recurrence, absolute eosinophil counts were above 0.5 x10 9 /L in all cases (n=4). This study broadens the spectrum of vascular manifestations associated with hypereosinophilia by adding ophthalmic vascular manifestations. In patients with ophthalmological vascular manifestations and hypereosinophilia, aggressive treatment of the underlying pathology (and normalization of blood count) should be implemented.